2021
DOI: 10.1155/2021/6397515
|View full text |Cite
|
Sign up to set email alerts
|

Board Financial Expertise and Corporate Cash Holdings: Moderating Role of Multiple Large Shareholders in Emerging Family Firms

Abstract: This study contributes to the literature by exploring the relationship between board financial expertise and cash holding policy and further showing how this relation is moderated by multiple large shareholders (MLS). This research is based on agency theory, resource dependence, trade-off, and pecking order theory to confirm how resourceful directors screen cash holding practices. This study selects the 100 listed family firms from the emerging economy of Pakistan for the period of 2006–2017. With the use of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 159 publications
(263 reference statements)
2
8
0
Order By: Relevance
“…Table 4 shows that the board size has a significant and negative relationship with cash holdings (β = -0.0034, p=0.052). This result is consistent with the previous study by Chen & Wang and MengYun, Husnain, Sarwar, & Ali, and Cambrea, Calabrò, La Rocca, & Paolone, [12,15,32] discovered a negative and significant correlation between board size and cash holdings. As a result, the first hypothesis (H1) is approved.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Table 4 shows that the board size has a significant and negative relationship with cash holdings (β = -0.0034, p=0.052). This result is consistent with the previous study by Chen & Wang and MengYun, Husnain, Sarwar, & Ali, and Cambrea, Calabrò, La Rocca, & Paolone, [12,15,32] discovered a negative and significant correlation between board size and cash holdings. As a result, the first hypothesis (H1) is approved.…”
Section: Resultssupporting
confidence: 93%
“…As show in Table 4, there is significant and positive relationship between board gender and cash holdings (β =0.1939, p=0.000). The result is in-line with Alghadi, Mazlan, & Azhari, and MengYun, Husnain, Sarwar, & Ali, [3,32] who found that board gender was significantly related with cash holdings. According to tradeoff theory, which is based on the cost-benefit tradeoff, corporations with more females on their boards of directors tend to hold the optimal amount of cash.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations